The (im)possibilities of public atheism in Indonesia: legal perspectives and social practices - Duile, Timo (Advances in South-East Asian Studies, 2024)
Indonesian society is, in large part, deeply religious. The notion of a divine entity (Ketuhanan yang Maha Esa) is the first principle of the Pancasila, Indonesia’s founding philosophy, also referred to as philosofische grondslag (philosophical basis) by Sukarno or Staatsfundamentalnorm (fundamental norm of the state) by the Indonesian Constitutio-nal Court. While a limited religious pluralism characterizes Indonesian society, atheism has often been portrayed as something alien or as a threat to the state and society, espe-cially in the so-called New Order era (1967–1998). While studies stress that Indonesia’s society has become increasingly conservative in recent years, cases of public atheism have also emerged. This article sheds light on these cases and demonstrates that this cont-roversial issue has been normalized in social media groups, or in other public forums, where people approach atheism with serious, educational debates or humor and irony. As Indonesia’s state and society can be described with analytical concepts, like ‘godly na-tionalism’, ‘religious harmony state’, and ‘plural society’, public atheism can illuminate how these concepts are challenged but also, to a certain extent, incorporate atheism as their antithesis. How atheism is publicly debated demonstrates how Indonesia’s religious plural society in its post-Reformasi era has reconceptualized atheism from a latent threat to an at least partially accepted social phenomenon.(ASEAS / GIGA)